Boost Converter Performance Improvement for Solar Panels Using Sliding Mode Controller - Nurwati, Tri; Wijono, Wijono; Hikam, Aldi Lutfil; Hasanah, Rini Nur (Faculty of Engineering, Universitas Brawijaya, 2021)
One way to utilize renewable energy sources is by using solar cells that convert sunlight energy into electrical energy. A converter is generally needed to adjust the output voltage of the solar cell to the application's needs. One type of converter that can be used is a boost converter, which can produce a voltage level at its output higher than its input. The output of the solar cell varies depending on changes in sunlight irradiation, which becomes the input for the converter. In this study, the sliding mode control (SMC) method is used to reduce oscillations in the boost converter's output voltage. The study was conducted by means of simulations using MATLAB/Simulink in open-loop and closed-loop control system conditions. The settling time value and the difference in output voltage before and after the disturbance occurred in the form of varying input voltages and varying loads were analyzed. Abstrak - Indonesia Salah satu cara memanfaatkan sumber energi terbarukan adalah dengan menggunakan sel surya yang mengubah energi cahaya matahari menjadi energi listrik. Sebuah converter umumnya diperlukan untuk menyesuaikan tegangan keluaran sel surya dengan kebutuhan aplikasinya. Salah satu jenis konverter yang dapat digunakan yaitu konverter boost, yang dapat menghasilkan tingkat tegangan pada keluarannya lebih tinggi dari masukannya. Keluaran dari sel surya yang bervariasi tergantung pada perubahan iradiasi cahaya matahari menjadi masukan bagi konverter. Pada penelitian ini metode pengendalian sliding mode control (SMC) dimanfaatkan untuk mengurangi osilasi pada tegangan keluaran konverter boost. Penelitian dilakukan dengan cara simulasi menggunakan MATLAB/Simulink pada kondisi sistem pengendalian loop terbuka dan loop tertutup. Nilai settling time dan selisih tegangan keluaran saat sebelum terjadi gangguan dan setelah terjadi gangguan berupa tegangan masukan yang bervariasi dan beban yang bervariasi dianalisis.